Electron flow in hydrogenotrophic methanogens under nickel limitation - Shunsuke Nomura; Pablo San Segundo-Acosta; Evgenii Protasov; Masanori Kaneko; Jörg Kahnt; Bonnie J. Murphy; Seigo Shima (Nature, 2025)
Abstract Methanogenic archaea are the main producers of the potent greenhouse gas methane1,2. In the methanogenic pathway from CO2 and H2 studied under laboratory conditions, low-potential electrons for CO2 reduction are generated by a flavin-based electron-bifurcation reaction catalysed by heterodisulfide reductase (Hdr) complexed with the associated [NiFe]-hydrogenase (Mvh)3–5. F420-reducing [NiFe]-hydrogenase (Frh) provides electrons to the methanogenic pathway through the electron carrier F420 (ref. 6). Here we report that under strictly nickel-limited conditions, in which the nickel concentration is similar to those often observed in natural habitats7–11, the production of both [NiFe]-hydrogenases in Methanothermobacter marburgensis is strongly downregulated. The Frh reaction is substituted by a coupled reaction with [Fe]-hydrogenase (Hmd), and the role of Mvh is taken over by F420-dependent electron-donating proteins (Elp). Thus, Hmd provides all electrons for the reducing metabolism under these nickel-limited conditions. Biochemical and structural characterization of Elp–Hdr complexes confirms the electronic interaction between Elp and Hdr. The conservation of the genes encoding Elp and Hmd in CO2-reducing hydrogenotrophic methanogens suggests that the Hmd system is an alternative pathway for electron flow in CO2-reducing hydrogenotrophic methanogens under nickel-limited conditions.